Invocavit Sunday sermon (1933)
This item is a Moravian sermon used for Invocavit Sunday, the first Sunday of Lent. It was originally given on March 5, 1933, but was edited and used again for Invocavit Sunday service in Makkovik on February 23, 1969. Title based on the contents of the record.